Physical oceanography and hydrochemistry measurements along ROV-Squid dive M183_30-1 during METEOR cruise M183 - Mario Esposito; Wolfgang Bach; Eric Pieter Achterberg (PANGAEA, 2023)
A sensor package for measuring and autonomously logging oceanographical parameters was installed on the ROV-Squid during the METEOR research cruise M183. The suite of sensors included an RBR Concerto logger for measurements of pressure, temperature, dissolved O? concentration and turbidity, a Pyroscience AquapHOx-LX for measurements of pH and a Trios OPUS nitrate sensor. The duration and frequency of the sampling were defined on every dive in order to have the best sensors performance/battery usage combination. Generally RBR Concerto data were recorded every 10 seconds, pH data every 30 seconds while nitrate data every 5 minutes. Following sensor post-calibration, a maximum pH offset of -0.05 was applied. Nitrate data were processed according to Nehir et al., 2021. While the RBR Concerto logger recorded during the entire dives, data for both the pH and nitrate sensors include bottom time and ROV ascent only.